Investigation of Displacement and Fracture Characteristics of Surrounding Rock under Strong Unloading Action. Issue 1 (1st December 2022) - Lin, Qindong; Feng, Chun; Gan, Yundan; Zhang, Yulei; Yuan, Jianfei; Jiang, Haiyan; Han, Lu
Abstract: The rock burst causes a significant threat to the construction of the deep-buried tunnel, and the displacement and fracture evolution characteristics of surrounding rock are investigated during the rock burst. First, the full-time numerical simulation of the rock burst is conducted. Then, the displacement evolution characteristic of the rock is analyzed. Finally, the fracture evolution characteristic of the rock is analyzed. The results indicate that more and more surrounding rock near the left straight-wall segment undergoes fracture and movement with the increase of time, and the rock that heaps up in the tunnel mainly comes from the middle-upper part. With the increase of time, the volume V r of rock moving into the tunnel and the fracture ratio α keep increasing, while the growth trends of V r and α decay. The fracture degree of rock near the left straight-wall segment is the most severe, and the fracture area gradually expands with the increase of time.